Ambiguity aversion and variance premium - Jianjun Miao; Bin Wei; Hao Zhou (Federal Reserve Bank of Atlanta, 2018)
This paper offers an ambiguity-based interpretation of variance premium - the difference between risk-neutral and objective expectations of market return variance - as a compounding effect of both belief distortion and variance differential regarding the uncertain economic regimes. Our approach endogenously generates variance premium without imposing exogenous stochastic volatility or jumps in consumption process. Such a framework can reasonably match the mean variance premium as well as the mean equity premium, equity volatility, and the mean risk-free rate in the data. We find that about 96 percent of the mean variance premium can be attributed to ambiguity aversion. Applying the model to historical consumption data, we find that variance premium mostly captures depressions, deep recessions, and financial panics, with a postwar peak in 2009.
Keywords: G12; G13; D81; E44; 330; ambiguity aversion; learning; variance premium; regime shift; belief distortion